If f(x) = 1/(6x^2), where x not equal to 0, find the rate of change when x=4.

f(x) can be rearranged to be: f(x) = 1/6 x-2This is then differentiated to be: f'(x) = -1/3 x-3 as the expression is multiplied by the original power (-2) and then the power is reduced by 1 (to -3)
f'(x) is then rearranged to be f'(x) = -1/(3x3) which x=4 can then be substituted into giving:
f'(4) = -1/(3*43) = -1/192

Answered by Thomas R. Maths tutor

1010 Views

See similar Maths Scottish Highers tutors

Related Maths Scottish Highers answers

All answers ▸

what is 87% of 654


The line, L, makes an angle of 30 degrees with the positive direction of the x-axis. Find the equation of the line perpendicular to L, passing through (0,-4).


Calculate the rate of change of d(t )=2/(3t), t ≠ 0, when t=6.


Solve algebraically the following system of equations: 4x + 5y = -3; 6x - 2y = 5


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences